Time and Cost Analysis on Building Construction Project using Crashing Method - Mohammad Fadli Dermawan; Ricky Sugiarto; Teguh Santosa; Niko Rozi (CV. Syntax Corporation Indonesia, 2024)
Crashing method is an effort to shorten the duration of a project by accelerating the work, Building Construction in Bogor can be built with the Crashing Method to save time and minimize costs. The purpose of this study was to determine the use of the Crashing method in building construction activities, and to determine the effect of duration on the addition of heavy construction equipment on the completion of faster 1st floor, 2nd floor, and 3rd floor work. The method used is field observation, this type of research is included in the type of comparative research. Based on the results of this study, the costs incurred have decreased compared to the previous cost of Rp. 1,477,760,967.01. It is known that the Normal Cost is Rp. 26,819,720,000.00 after doing the calculation, the Crashing Cost is Rp. 25,179,405,907.94. In the calculation of the amount of Normal Cost labor of Rp. 841,309,890.35 and Crashing labor of Rp. 633,974,914.30 for total normal materials of Rp. 3,212,062,893.19. Crashing materials totaled Rp. 2,361,951,475.67. In the calculation of the duration with the addition of Concrate Pump equipment on the K-300 concrete work of the 1st floor, 2nd floor, and 3rd floor, the duration of 14 days is accelerated, the normal duration is known to be 210 days after crashing the results of the duration of 196 days.